Quantification of the influence of varying electrode shapes and materials on the thermo-crimping process of standardized tubular cable lugs - Spreng, Simon; Gläßel, Tobias; Muselmann, Johannes; Wörrlein, Marina; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
The main joining task in the field of electric drives production is to connect bundles of insulated copper wires with standardized tubular cable lugs, as this connection alternative is widely used in all types of different electrical stator varieties. Implementing this process in industrial production facilities, the thermo-crimping technology is widely used. Within this technique, the insulation is thermally destroyed, while coincidently, the tubular cable lug and the inlying skinned copper wires are deformed plastically, which generates a force fit crimp-connection. The thermo-crimping process features strong production-related benefits such as short tact times, high process reliabilities as well as an easy process handling. The severe disadvantage however has to be seen within the electrode wearing, as the crimping tools are simultaneously exposed to high pressures and temperatures of at least 600 C reducing an electrode's number of possible crimping routines to at most 1500. As a consequence, especially in serial production, excessive maintenance efforts have to be taken into account, strongly reducing the production efficiency. For this purpose, the institute FAPS focuses its research on the reduction of tool wearing. Beginning with a theoretical process analysis, different tool shapes and materials are compared experimentally considering both, the joint quality and the electrode wearing. Subsequently, regression models are introduced predicting static quality properties such as tensile forces and transition resistances. Finally, the proposed model is validated by applying the found formula to different cable lug sizes.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric drives manufacturing; thermo crimping; varying electrode shapes